Hypertonic Saline Therapy in Cystic Fibrosis: Do Population Shifts Caused by the Osmotic Sensitivity of Infecting Bacteria Explain the Effectiveness of this Treatment? - Williams, Huw D.; Behrends, Volker; Bundy, Jacob G.; Ryall, Ben; Zlosnik, James E. (Frontiers in Microbiology, 2010)
Cystic fibrosis is caused by a defect in the CF transmembrane regulator (CFTR) that leads to depletion and dehydration of the airway surface liquid (ASL) of the lung epithelium, providing an environment that can be infected by bacteria leading to increased morbidity and mortality. Pseudomonas aeruginosa chronically infects more than 80% of CF patients and one hallmark of infection is the emergence of a mucoid phenotype associated with a worsening prognosis and more rapid decline in lung function. Hypertonic saline (HS) is a clinically proven treatment that improves mucociliary clearance through partial re-hydration of the ASL of the lung. Strikingly, while HS therapy does not alter the prevalence of P. aeruginosa in the CF lung it does decrease the frequency of episodes of acute, severe illness known as infective exacerbations, among CF patients. In this article, we propose a hypothesis whereby the positive clinical effects of HS treatment are explained by the osmotic sensitivity of the mucoid sub-population of P. aeruginosa in the CF lung leading to selection against this group in favour of the osmotically-resistant non–mucoid variants.